Cultural Representation in International Media: Trends and Implications - Dembe, James (Journal of Communication, 2024)
Purpose: The general objective of this study was to understand cultural representation in international media exploring the trends and implications. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to cultural representation in international media. Preliminary empirical review revealed that cultural representation in international media had significantly transformed over the past decade, driven by societal changes and demands for inclusivity. Despite progress, challenges remained in achieving equitable representation, especially behind the scenes. Positive trends had implications for social cohesion, economic outcomes, and individual self-perceptions, while persistent stereotypes and biased portrayals continued to undermine these benefits. The study emphasized the importance of ongoing efforts to promote diversity and accurate portrayals to foster a media landscape that truly reflects global diversity and contributes to understanding and social harmony. Unique Contribution to Theory, Practice and Policy: The Social Identity Theory, Cultivation Theory and Framing Theory may be used to anchor future studies on cultural representation in international media. The study recommended expanding theoretical frameworks to include intersectionality, critical race theory, and feminist theory to better analyze media representation. Practically, it advised media producers to adopt inclusive casting and storytelling practices, implement mentorship programs, and conduct regular diversity audits. Policy recommendations included stronger regulations and incentives for diversity, along with monitoring systemic biases. Specific industry strategies were suggested for different media sectors, such as collaborating with cultural consultants and designing algorithms to promote diverse content. Educational initiatives included integrating diversity courses in academic programs and providing bias training for professionals. Finally, the study emphasized the need for global collaboration and ongoing research to monitor trends and assess the impact of representation initiatives.